(untitled) (Bangladesh Journal of Bioethics, 2013)
Patients with life-limiting illness and their families face many problems and complexities. The gravity of such problem is often escalated with the fact of the patients deprivation of the proper care as a corollary to their fundamental health rights. The legal aspects of the palliative care thus concern the issues of concentrating more on the rights of the patients in getting relief from sufferings of all kinds, physical, psychological and spiritual. As such, it may include the opportunity of getting legal interventions not only in the way of claiming the protection of palliative care (such as securing access to health and social benefits) but also in the face of dealing with other life-transactions of the patients and their families (such as protecting and disposing of property; planning for children and other dependents). This paper is an attempt to articulate these legal dimensions of the right to palliative care in the context of Bangladesh. The major focus of this paper will be founded on the wide-ranging constitutional obligation on the right to health, which offers a meaningful space for the right to palliative care by way of implications. More importantly, this paper will clarify the point that taking the right to palliative care seriously will at least result in sensitizing the health right of the people of Bangladesh, especially for the poor communities, having limited awareness of their human rights and limited access to and little experience of legal services. DOI: http://dx.doi.org/10.3329/bioethics.v4i3.17375 Bangladesh Journal of Bioethics 2013; 4(3):25-33